A laboratory system for modeling hay storage - W.K. Coblentz; J.O. Fritz; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1993)
A simple system is described that uses a hinged metal baling unit and a hydraulic press to make 4.0 x 4.3 x 5.3 inch wire-tied, laboratory- scale, hay bales. A comparison of densities of conventional, small, alfalfa bales (15x18x37 inches) and laboratory bales was made over a wide range of moisture levels (15 to 36%) and conventional bale densities (10 to 25 lb/ft3). Laboratory bale densities were regressed against conventional bale densities and agreement was excellent. The system is inexpensive to build and easy to use and can be reproduced easily.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Hay; Bale; Laboratory-scale; Alfalfa